2020
DOI: 10.1002/ieam.4227
|View full text |Cite
|
Sign up to set email alerts
|

Tailings from Fundão Tragedy: Physical–Chemical Properties of the Material That Remains by Candonga Dam

Abstract: In this work, samples of Fe mining tailings from the collapsed Fundão Dam, Brazil, which were retained by the Candonga hydroelectric power plant, were characterized by various techniques. Quartz, hematite, kaolinite, and goethite were identified as the main phases present. The composition, homogeneity, and relatively low (~1%) organic matter content indicate potential for usage of these tailings in civil constructions. The next step of this work is to investigate such applications. If their feasibility is conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
16
0
4

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 13 publications
3
16
0
4
Order By: Relevance
“…The elevation of Fe and Al concentrations is due to the fact that the tailings stored in the Fundão dam were composed of hematite, kaolinite, goethite, and quartz, presenting about 60% of Fe, 14% of Si, and 2% of Al (Pires et al, 2003). In a recent characterization of the tailings, Figueiredo et al (2020) reported the presence of other elements such as potassium (K), magnesium (Mg), calcium (Ca), titanium (Ti), sodium (Na), Mn, phosphorus (P), and chromium (Cr).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of Fe and Al concentrations is due to the fact that the tailings stored in the Fundão dam were composed of hematite, kaolinite, goethite, and quartz, presenting about 60% of Fe, 14% of Si, and 2% of Al (Pires et al, 2003). In a recent characterization of the tailings, Figueiredo et al (2020) reported the presence of other elements such as potassium (K), magnesium (Mg), calcium (Ca), titanium (Ti), sodium (Na), Mn, phosphorus (P), and chromium (Cr).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings regarding bioaccumulation of metals in soft tissues of C. fluminea evidenced the incorporation of some elements, but in a very limited way, as the BAFs tended to be low and only occasionally were considered relevant. Relevant bioaccumulation of Cu and Zn was more frequent (Table 2), but these elements are not related to the tailings (Figueiredo et al, 2020), and it is well known that bivalves naturally accumulate Cu and Zn in their tissues. In addition, organisms exposed to sediments from Manhuaçu, a reference site not affected by the tailings, showed relevant BAFs.…”
Section: Discussionmentioning
confidence: 99%
“…Overall effects of the ore tailings on metals and arsenic concentrations in fish Among the twelve chemical elements analyzed in fish muscle tissue, As showed the highest concentratios in fishes from sites affected by the ore tailings released by the SAMARCO/BHP Billiton/Vale's dam rupture compared to fish from control sites in seven out of nine analyzed fish species; while Zn showed higher concentrations for two out of nine species (Table 2). As far as these two elements are in low concentrations in the ore tailings, compared to their regional level outside the river (Figueiredo et al 2020), we interpret the higher concentrations of these elements in fish tissue as resulting from a higher bioavailability of Arsenic and Zinc launched by the ore tailings' physicochemical effects on the river bottom's sediment.…”
Section: Discussionmentioning
confidence: 90%
“…In rivers, finer sediments generally accumulate in low energy environments, which would be predominant in Doce River's tributaries rather than its main channel ), but the SAMARCO's dam rupture launched ore tailings avalanche altered this condition. After the avalanche, the bottom of the Doce River channel presented a different situation, because the tailings buried the former River bottom with a slur mainly composed of anthropogenic, extremely fine, sediments of silt and clay, with lower concentration of organic matter, compared to the unaffected tributaries, resulting in unnatural river conditions (Figueiredo et al 2020;dos Reis et al 2020). Adsorption and absorption of contaminants to sediments depends on the relative contents of organic matter and clay per surface area (Streit, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Algumas das percepções dos/as agricultores/as estão de acordo com as características do rejeito, que apresenta baixo teor de nutrientes, o que dificulta a nutrição de plantas, baixo teor de carbono orgânico, que dificulta os processos físicos, químicos e biológicos do solo, granulometria fina, que dificulta a infiltração de água Figueiredo et al, 2019) e aumento dos teores de metais como ferro, manganês, cobre e crômio, que podem ser tóxicos para as plantas (Mariana et al, 2017;.…”
Section: áGuaunclassified